2004
DOI: 10.1002/pssa.200304903
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fullerene-like CNx thin films deposited by pulsed-laser ablation of graphite in nitrogen

Abstract: Fullerene‐like CNx thin films were synthesized by Pulsed‐Laser Ablation (PLA) of pyrolythic graphite (99.99%) target in nitrogen using a (500 mJ, 7 ns, 1064 nm) Nd:YAG‐pulsed laser. The films were deposited onto silicon substrates at 300 °C and nitrogen pressures within the 5–100 mTorr range. The composition and structure of these films were analyzed by means of Reflection Absorption Infrared Spectroscopy (RAIRS), XPS, and Raman spectroscopy and the morphology of the film surfaces by AFM. The RAIRS analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In fact, films grown at 5 mTorr presented the highest N content (23%) and P 2 /P 3 ratio (1.41), for N 1s nitrogen bonding and the highest Raman I(D)/I(G) ratio (2.45), related to the lowest G-peak position (1548.1 cm −1 ). These results indicate highest fullerene likeness under our experimental conditions [12]. …”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In fact, films grown at 5 mTorr presented the highest N content (23%) and P 2 /P 3 ratio (1.41), for N 1s nitrogen bonding and the highest Raman I(D)/I(G) ratio (2.45), related to the lowest G-peak position (1548.1 cm −1 ). These results indicate highest fullerene likeness under our experimental conditions [12]. …”
Section: Resultssupporting
confidence: 66%
“…This result can be correlated to the N/C ratio of deposited CNx films, calculated using the ratio between the N 1s and C 1s peaks obtained through X-ray Photoemission Spectroscopy (XPS). We found that nitrogen content decreased from 23% to 18%, as pressure was increased from 5 to 30 mTorr [12]. In order to determine formation mechanisms, we have estimated the vibrational temperature of CN molecules using a relative emission intensity method.…”
Section: Resultsmentioning
confidence: 99%
“…High-resolution XPS analysis shows three distinct peaks at 398.6, 400.9, and 404.9 eV (Supporting Information). The peak at 398.6 eV is commonly attributed to pyridinic-type nitrogen, , and the peak at 400.9 eV is attributed to a convolution of both pyrrolic/pyridonic and quaternary functionalities, the former at 400 eV and the latter at 401 eV. ,, The assignment of the peak at 404.9 eV is unclear and could be attributed to chemisorbed N-oxides, ,, pyridinic oxides, , molecular N 2 , , or shakeup satellites. , This peak cannot be assigned to one single functionality and is instead possibly a convolution of various possible coordinations. Heat treatment experiments were undertaken to determine the effect of removable surface N-oxides on the total nitrogen content.…”
Section: Resultsmentioning
confidence: 99%
“…For the film S1, the sp 2 peak at 284.6 eV in C 1s spectrum is close to that of nitrogen-free amorphous carbon film (284.5 eV) deposited under similar conditions, but the sp 3 peak at 285.8 eV is higher than that of carbon film (285.3 eV), for the sp 3 peak of b-C 3 N 4 is at 287.6 eV [17]. Correspondingly, in the N 1s spectrum, the peak at 398.6 eV is ascribed to N-C bond and that at 400.4 eV is to N@C bond [18].…”
Section: Resultsmentioning
confidence: 85%